QUALITY OF LIFE AMONG END-OF-LIFE FORMER COMMERCIAL PLASMA DONORS INFECTED WITH HIV IN RURAL HENAN, CHINA. Issue 2 (1st June 2013) - Sheng, Y; Qiu, Z; He, Y; Zhang, Y
Abstract : Background: China has began providing antiretroviral therapy to people living with HIV/AIDS (PLWHA) since 2003. Aim: Purpose of present study was to investigate quality of life and happiness, as well as their needs in hospice care at their end-of-life among HIV-positive people in rural Henan. Methods: One-hundred AIDS patients at their end-of –life were selected from Weishi, Zhenping and Tanghe counties, Henan province of middle China using convenience sampling. WHO Quality of Life for HIV (WHOQOL-HIV) BREF Chinese version was used to measure their quality of life, and Memorial University of Newfoundland Scale of Happiness (MUNSH) was used to measure their subjective welfare. Personal in-depth interview and focus group discussion were used to learn their needs for hospice care at end-of-life of the patients. Results: Overall quality of life was moderate among the patients with an average score of 12.62 and SD of 1.97, higher in domains of spirituality, religion and personal belief (with an average score of 14.40±2.96) and psychological domain (13.58±2.06), and lower in independence (12.15±2.15) and environment (12.50±3.28) domains. Average MUNSH score was 21.00±6.20, with moderate range. Discussion and Conclusion: Palliative care model used was beneficial to the patients. In-depth interviews indicated that Henan provincial government's policy of treatment and care for AIDS patients has had a beneficial impact on them at their end-of-life overall, although care component could be improved further by assisting their families as a whole.